Implementasi Program Bimbingan Belajar “Ahad Skuy” dalam Mendorong Moderasi Agama di Desa Kebonrejo Kabupaten Kediri - Nurul Fadilah; Asy'ari; Anggi Esty Rachmanika; Salma Salsabila (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
This article aims to analyze the impact of the Real Work Lecture (Kuliah Kerja Nyata or KKN) program on religious modernization in Kebonrejo Village, Kepung District, Kediri Regency. Kebonrejo Village is a predominantly Islamic village, but its community still holds traditional understandings of Islam. The KKN program implemented in Kebonrejo Village aims to enhance religious tolerance in community life. The research uses the Participatory Action Research (PAR) method, which involves the community in the research process. In this study, the Kebonrejo Village community participates in the planning, implementation, and evaluation of the KKN program. The results of the research show that the KKN program conducted in Kebonrejo Village has had a positive impact on religious moderation in the village. The Kebonrejo Village community now has a better understanding of Islamic teachings that can bridge the differences within the society, leading to increased tolerance towards religious diversity.